Out-of-plane analysis of dry-stone walls using a pseudo-static experimental and numerical approach in scaled-down specimens - Santa-Cruz, Sandra; Daudon, Dominique; Tarque, Nicola; Zanelli, Criss; Alcántara, Julio (Elsevier, 2021)
The objective of the present work is to study the response of dry stone walls subjected to out-of-plane forces and the influence of block`s rugosity, joint arrangement, and border conditions. For this purpose, a series of scaled-down experimental tests on a tilting table and 3D numerical modelling using discrete elements, DEM, are proposed. In the numerical model, the applicability of some types of discrete elements is first studied. The preliminary analysis gives us useful information about the effects of the joint disposition and the border conditions in the response. Finally, the sensitivity of the response of the blocks to the parameter’s variations is analyzed. The experimental and numerical results show that the DEM method is adequate to simulate the failure mode, the displacement, and the lateral load of stone walls due to out-of-plane lateral loads considering the effect of the irregularity of the blocks, joint arrangement, and border conditions.
Keywords: Masonry; Numerical modelling; Walls; DEM; YADE; Earthquake; Tilting table; https://purl.org/pe-repo/ocde/ford#2.01.01